Determination of total protein content in white wines by solid phase spectrometry in a SI–LOV system - Vidigal, Susana S. M. P. (2013)
Although present at low concentration in wine samples, proteins, have considerable technological importance, due to their capability of haze formation. The present work presents a methodology for the quantification of total protein in white wine in a sequential injection lab-on-valve system, exploiting the bead injection concept for solid phase extraction with spectrophotometric detection. The method is based on the retention of the proteins in the solid support, NTA (nitrilotriacetic acid) superflow beads, charged by Cu2+. The change in the absorbance is monitored at 500 nm at the surface of the beads after addition of the Folin–Ciocalteu’s reagent (FCr). The developed method presented a sample consumption of 400 L per assay and a consumption of FCr and Cu2+ solution of 25 L and 100 L per assay, respectively. It was possible to achieve a linear range up to 0.30 g/L with a limit of detection and quantification of 0.03 and 0.10 g/L, respectively. The proposed method was successfully applied to white wine samples.